DEVELOPMENT AND QUALITY EVALUATION OF PREBIOTIC YOGHURT FROM GOAT MILK - K.R. Megha; K. Radha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
An effort was made to develop functional yoghurt from goat milk by incorporating prebiotic component inulin at 0.5 and 1% level. The goat milk yoghurt without added inulin was used as control sample. The developed functional goat milk yoghurt and control were analysed for physico-chemical, microbiological and sensory qualities by standard procedures. Addition of inulin enhanced the Lactobacillus count of yoghurt samples. Apart from this prebiotic property, inulin was found to have an effect on controlling the development of acidity. Titratable acidity of inulin added yoghurt (1%) was within the legally permissible limit up to two weeks of refrigerated storage; whereas, in control yoghurt, acidity was within the permissible limit up to one week only. Inulin added samples obtained better sensory scores than the control. The addition of inulin to goat milk yoghurt contributed to the improvement of rheological characteristics of the product.